Factors affecting blood donation intervals and patterns of return based on a sample in southern Iran: A follow-up design - Salman Daneshi; Esmat Rezabeigi Davarani; Farhad Arefi; Fateme Jahangiri Mehr; Kiavash Hushmandi; Mehdi Raei; Reza Fariabi; Mohadeseh Shojaei Shahrokhabadi (Russian Open Medical Journal)
Objectives — The main goal of blood transfusion centers is to recruit and retain more qualified blood donors. This study aimed to identify the factors influencing the return of volunteer blood donors. Material and Methods — A cohort study was conducted on all blood donors who donated blood for the first time, from March 21, 2013, to March 20, 2014. They were followed up for five years (up to March 20, 2018). Demographic characteristics, type of blood donation and time interval between two blood donations were recorded as recurrent events. Data were then analyzed using Logit Model for Multinomial Responses and Cox's shared frailty model. Results — Of the 2010 blood donors, 33.7% as the repeated donor and 16.2% as the regular donor had regular donations. The frequency of blood donation was in the range of 1 to 20 with a mean of 4.54±3.29. There was a significant reverse relationship between the number of donations and the time interval between two donations. The variables of gender, marital status and occupation had a significant effect on the blood donation of the repeated and regular donors. Genders, age at the time of the first donation, marital status and occupation had a significant effect on the intervals between blood donations. Conclusions — Most of blood supply of Iran is provided by men and first-time donors. Since the decision to donate and keep donating blood involves many complex issues applied programs are require to convert women and first-time donors into regular donors.